MEDICAL JOURNALISM IN THE WORLD HEALTH ORGANIZATION EASTERN MEDITERRANEAN REGION - Habibzadeh, Farrokh (Journal of Postgraduate Medical Institute, 2012)
The Middle East is known as the cradle of life. Over the past centuries numerous erudite scholarsin various scientific disciplines were raised from this region and handed the torch of scientific enterpriseover to their descendants1. However, after a while the scientific centers have gradually moved from thisregion to the West, hence, the aphorism ex oriente lux2. The shift in scientific centers from East to the Westhad several reasons the most important of which were probably the atmosphere of la belle indifférenceamong people of the region and concomitant beginning of the Renaissance and the Age of Enlightenmentin the West.